ChemInform Abstract: Ligand‐Controlled Palladium‐Catalyzed Alkoxycarbonylation of Allenes: Regioselective Synthesis of α, β‐ and β, γ‐Unsaturated Esters. Issue 51 (December 2015) - Liu, Jie; Liu, Qiang; Franke, Robert; Jackstell, Ralf; Beller, Matthias
Abstract: The first general carbonylation reaction of various allenes with aliphatic alcohols is presented.